Obnova upravnega postopka zoper sklep - Žuber, Bruna (Javna uprava, 2017)
In practice, the renewal of the proceeding is one of the most frequently used extraordinary legal remedies in the administrative procedure. One of the basic conditions for a renewal of a proceeding is that the proceeding was completed with a final decision on the merit against which there is no regular remedy in the administrative procedure. The rule that the renewal of a proceeding against an order issued in an administrative procedure is inadmissible should, without exception, apply to all procedural orders. Different treatment should apply only to those orders that are decisions on the merit in their content. An assessment on a legal nature of an order should be performed exclusively on the basis of operative part of the decision with awareness that extension of a renewal of the proceeding in concrete cases against procedural orders is not permissible. An arrangement that does not provide the renewal of proceedings against an order does not constitute an unreasonable restriction to the access to a legal remedy.
Keywords: obnova upravnega postopka; odločbe; procedural order; procesni sklep; the renewal of administrative proceeding; upravni postopek